2019
DOI: 10.1007/s11368-019-02447-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of fallout and geogenic radionuclides as potential tracing properties to quantify the sources of suspended sediment in a mining catchment in New Caledonia, South Pacific

Abstract: Open-cast mining has strongly increased soil erosion and the subsequent downstream transfer of sediments in river systems resulting in fundamental morphological changes (e.g. hyper-sedimentation, over-burden). Understanding the sediment source contributions from mining activities is therefore important to guide the implementation of effective management measures. Materials and methods. A pilot sediment tracing study was conducted in the Thio River (400 km 2) catchment draining the island's first mine. Sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
0
19
1
Order By: Relevance
“…Particle size sorting may be at the origin of the nonconservation of some tracer properties (Laceby et al, 2017). Nevertheless, the previous results obtained in Sellier et al (2020) demonstrated that 11 geochemical tracers analyzed in the current research were not significantly impacted by particle size effect. According to the range test results, all properties (except Fe) were found to be conservative.…”
Section: Source Conservation and Discriminationcontrasting
confidence: 57%
See 2 more Smart Citations
“…Particle size sorting may be at the origin of the nonconservation of some tracer properties (Laceby et al, 2017). Nevertheless, the previous results obtained in Sellier et al (2020) demonstrated that 11 geochemical tracers analyzed in the current research were not significantly impacted by particle size effect. According to the range test results, all properties (except Fe) were found to be conservative.…”
Section: Source Conservation and Discriminationcontrasting
confidence: 57%
“…In New Caledonia, a sediment fingerprinting approach had previously been developed to quantify sediment source contributions over two cyclonic events (Sellier et al, 2020). In this approach, the use of geochemical elements such as K to trace mining versus non-mining tributary contributions is supported by the characteristics of the lithological material where both source types are found.…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…One exception was a mining catchment of New Caledonia, South Pacific Islands, where the very low 137 Cs activities measured in mining and non-mining tributaries indicated the dominance of subsurface sources in the sediment contribution in this region. Given much higher activities were measured at similar latitudes in Australia, these low activities likely reflect the intensity of soil erosion processes and the dominance of subsoil erosion on this island (Sellier et al, 2019).…”
mentioning
confidence: 85%
“…Indeed, there has been a recent emphasis to justify the parameters selected by the three-step statistical procedure (e.g. Mukundan et al 2010 ; Vale et al 2016 ; Sellier et al 2020 ) and investigators are encouraged to adopt this level of scrutiny, rather than relying on statistical solutions alone (Collins et al 2017 ).…”
Section: Outstanding Issues Requiring Further Research and Consensusmentioning
confidence: 99%